Pelaksanaan Eksekusi Hadhonah Bagi Pasangan Yang Bercerai Di Pengadilan Agama Curup Tahun 2016 - Zainal Arifin (Institut Agama Islam Negeri Curup, 2018)
This research aims to give a identification about Hadhanah’s problems which were often separated with claims or divorce requests. The phenomenon of child custudy disputes for small regional areas such as in city of Curup is not understood yet by the public. The lack of understanding about it sometimes makes what has been decided by the court is not implemented by the parties concerned. This research was field research with qualitative approach. In assessing the primasy data obtained from the interview, the researcher used interative libraries such as the Alquran and hadith. From the research, it is found that, first the number of hadhanah’s case at Curupreligious court class I B in 2016 is one case with the case number 262/Pdt.G/2016/PA.Crp. Second, the exsecution of hadhanah’s case at curupreligious courts in class I B in 2016 has never been done because the public understanding of the execution is still lack, the cost of execution is quite expensive and the strength of family principles in solving problems. Last, the consistency of the level of execution ofhadhanah’s caseinCurup religious courts in class I B in 2016 can not be seen and can not be found. It is because there has never been any parties who have filed an appeal or a request for a cassation against hadhanah’s verdict.